MC1 --- Iterative Analysis of Spatio-temporal Data by Textual Queries and Visualizations - Beham, Michael; Podaras, Silvana; Splechtna, Rainer; GraCanin, Denis; Matkovic, Kresimir (2017 IEEE Conference on Visual Analytics Science and Technology (VAST), 2017)
Visualizing monitored traffic over a long period of time is a difficult problem. The trajectories of many traffic participants have to be taken into account to find regular patterns and unusual behavior. We introduce a novel system for visual analysis of spatio-temporal tracking data. This system, developed as response to VAST 2017 Mini-Challenge 1, enables iterative analysis steps by combining textual queries and linking and brushing interactive visualizations in ComVis tool.